The Use of Flashcard and Bbc Nature Video to Improve Students Ability in Writing Descriptive Text (A Comparative Study of Grade 10 SMA N 1 Bangun Purba Rokan Hulu in the Academic Year of 2023) - Dwi Indra Gusti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2023)
This final project is a comparative study in experimental design that aims at investigating whether there is any significant difference of the achievements in writing descriptive texts of students who are taught by using flashcards and those who are taught by using BBC Nature videos with an assumption that these media can help them to interpret the content of the course. The subjects of the study were the eight grade students of SMA N Bangun Purba, Rokan Hulu in the academic year of 2023. There were two groups that were given different treatments. The first group was the control group who was taught by using flashcards, and the second group was the experimental group who was taught by using BBC Nature videos. There were seven meetings for each class;one meeting was for the pre test, five meetings were for treatments and one meeting for the post test. In the test, the students of the control group used the flashcards and the experimental group used the BBC Nature videos to write a descriptive text based on the topic provided: animal. The result of this research showed that the pre-test average scores of the two groups were nearly the same. The means of the pre-tests were 65.07 (the control group) and 65.47 (the experimental group). The slight difference between the two groups indicated that they were similar learning basis. After the control and the experimental groups were given different treatments, the score of the two groups increased. The means turned into 76.67 for the control group and 84.00 for the experimental group. The improvement were 11.60 (the control group), and 18.53 (the experimental group). The result of t-test based on the difference of two means revealed that the obtained value (3.86) was higher than t-table value for α = 5% (2.00). It means that there was a significant difference between the students who were taught with flashcards and those who were taught with BBC Nature videos. Based on the result above, it is concluded that in this study BBC Nature videos are more effective than flashcards to improve students‟ ability in writing a descriptive text. It is suggested that video can be used as alternative media for teaching descriptive text. Further research is suggested to be carried out for a better understanding of this field.